Pathology of the problem of polygamy in Iranian law and procedure - Mahdieh Mohammad Taghizadeh; Zahra Hamidi Soha (زن در فرهنگ و هنر, 2017)
Over the past decade, the phenomenon of polygamy has received a great deal of attention from researchers. The point to be considered in the related explanations is the stubborn adoption of a position of defense or opposition to polygamy. For some polygamous people, it has been customary in the past, but it is now not common in most societies. For other groups, however, its prescription in religious texts has made polygamy sufficiently allowable. Given the fact that "polygamy", understood as “multiple marriages”, is subject to the existence of certain conditions (derived from sharia and law) for its realization, therefore, protection of women's rights, community health, direct and indirect consequences of polygamy on the family as the most fundamental institution of society dictates the importance of the legislator's attention to this issue. The present article, using the library method, with an analytical-descriptive and inferential approach, after examining polygamy in Islam and addressing the issue of the principle of "unilateralism", aims to examine its related laws in civil law and law support for the family. Finally, after chart analysis of 20 cases related to polygamy, the legal proposals are presented to support the consolidation of the family foundation and to protect the rights of women and children in families facing this problem, relying on the fact that it is necessary to present legitimate and justifiable reasons for marrying a second wife; and  the resignation of such marriage is subject to the existence of one of these reasons. Moreover, the reasons for the trial and also the specialized counseling body in the petitions which are due to non-compliance are in the text of the law.